The Association between ANXA11 Gene Polymorphisms and Sarcoidosis: a Meta-Analysis and systematic review - Zhou, Hongfei; Diao, Mengyuan; Zhang, Mingyue (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background and Objective: The associations of ANXA11 gene polymorphisms and susceptibility to sarcoidosis have been evaluated in recent years. However, the results remain controversial, especially in different ethnicity. To assess the associations between ANXA11 and sarcoidosis, we conducted this meta-analysis. Method: Articles were searched in MEDLINE, EMBASE and PubMed from their establishment date to August of 2014, and 4,567 sarcoidosis patients and 4,278 controls from 6 studies were included. The strength of associations was determined by ORs with 95% CIs. The associations between ANXA11 SNP rs1049550, rs2573346, rs2789679 polymorphisms and sarcoidosis risk were assessed using additive, recessive and dominant models. Results: ANXA11 SNP rs2573346 and rs2789679 T allele conferred protection against sarcoidosis (OR: 0.664, 95% CI: 0.607-0.726 for rs2573346, and OR: 0.698, 95% CI: 0.640-0.762 for rs2789679). For SNP rs1049550, individuals carrying the ‘‘T’’ allele (TT+CT) had a nearly 46% increased risk for the development of sarcoidosis, when compared with CC homozygotes (OR: 1.461, 95% CI: 1.183-1.803) in overall population. A significant association was also found in additive model (OR: 1.477, 95% CI: 1.328-1.642 for CC vs. CT; OR: 0.610, 95% CI: 0.412-0.905 for TT vs. CC). In addition, ethnicity factors may contribute to the disease risk. Conclusion: The meta-analysis revealed that ‘‘T’’ allele of ANXA11 SNP rs2573346 and rs2789679 conferred protection against sarcoidosis. ‘‘C’’ allele of SNP rs1049550 may be a risk factor for sarcoidosis in overall population. Our study shows that ANXA11 closely associated with the development of sarcoidosis but further studies in different ethnicity were needed.